Bellevalia bayburtensis (Asparagaceae): a new species from northeastern Anatolia, Turkey - Yildirim, Hasan; Sefali, Abdurrahman (Phytotaxa, 2020)
Bellevalia bayburtensis (Asparagaceae) is described and illustrated as a new species from Bayburt Province in northeastern Anatolia, Turkey. Diagnostic morphological characters, a full description, detailed illustrations, and a distribution map are provided. It is morphologically similar to B. rixii and B. paradoxa, but clearly differs from these species by the leaf shape, the bud and flower colour.